Sculptural proposals for the logos of the faculties of Iraqi Universities - an applied study - Hajar Ali Majeed; Mohsin Ali Hussain (Basrah Arts Journal, 2023)
The slogan is of great importance, as it is a message with significance related to a specific goal that refers to the viewer, and its structure may be a form, letter, word, or brief free linear elements, or a mixture between them, as the slogan has symbolic connotations that excite the recipient and affect his sensory perception this research sought to present sculptural proposals for the slogans of the faculties of the university of Basrah, and this study included four chapters. To him: the importance of this study is evident from the importance of designing the sculptural logo and its pivotal role in achieving the visual identity of the faculties of the university of Basrah. As for the limits of the research: the spatial limits: (Iraq - Basrah - Basrah university) the temporal limits (2022). Among the results reached by the researcher: 1. The researcher focused on the topic of simplicity and shorthand in the models of sculptural slogans proposed for the faculties of the university of Basrah, which work to attract the concept of diversity, unity, and symmetry because of the absolute methods they contain that depict the data of the geometric perception, and its dominant aesthetic action in the form of sculptural slogans.